PENGARUH INTENSITAS KONSUMSI BERITA PENIPUAN 1-C OMMERCE DAN INTENSITAS KOMUNIKASI KELOMPOK RUJUKAN TERHADAP TINGKAT MINAT BELI PADA SITUS BELANJA ONLINE TOKOPEDIA - Ranni Arismaya Handayaningtyas; Sunarto . (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
The development of increasingly advanced technology allows a person to make online shopping purchases on an e-commerce site as a mediator. E-commerce activities that are not directly face-to-face with buyers and sellers, in online buying and selling in e-commerce will make a risk assumption. The number of fraud problems that occur in online buying and selling this affects both sellers and buyers, with the emergence of such cases will make buyers and sellers more cautious in making trades through online media. The purpose of this study is to explain the influence of e-commerce fraud news consumption intensity and communication intensity of reference group on purchasing interest level on tokopedia online shopping site. The theory used is Uses and Gratification. The type of research that quantitative research uses with explanatory survey research methods. Sampling used non-probability sampling. The sample in this study amounted to 30 respondents with male and female characterization based in Tembalang sub-district of Semarang. Analyze data using linear regression tests. The results showed there was an influence of e-commerce fraud news consumption intensity and communication intensity of reference group on purchasing interest level on tokopeida onine shopping site. This is supported by the calculation of the X1 variable correlation coefficient of 0.400 and the X1 regression coefficient of 0.296 which states that each increase in variable X1 then Y will increase or affect by 0.296 or 29.6%. The results of the second hypothesis showed there was an influence of e-commerce fraud news consumption intensity on purchasing interest level on tokopedia online shopping site as evidenced by the correlation coefficient for variable X2 of 1,056 which showed a large rated r-value of the r-value table (0.361) and the X2 correlation coefficient of 0.475 which states that each X2 variable increase will have an effect of 0.475 or 49.5%. The results of variable e-commerce fraud news consumption intensity and the intensity of referral group communication suggest both have a significant relationship to variable level on tokopedia online shopping site. Meanwhile, spss test results obtained by Ry(1,2) (0.806) have a calculated value greater than the number value in the table (0.361).